Balancing Rural Development and Corporate Image: Evidence From Social Responsibility Performance in Agriculture Program of Mining Company - Sitompul, Firdaus Marihot; Simanjuntak, Megawati; Nurhayati, Popong (Jurnal Manajemen dan Agribisnis, 2024)
Background: Mining companies naturally have the potential to harm the environment, and CSR is a step towards achieving a good image. The harmony and balance between corporate image and rural development through social welfare indicators is an essential aspect of mining companies’ CSR practices. Purpose: This study aims to analyze the performance of the agriculture CSR program on the corporate image and social welfare of mining companies. Design/methodology/approach: Using Structural Equation Modeling (SEM) analysis techniques based on partial least squares (PLS), this study employed purposive sampling to determine the research sample based on one criterion. The sample consisted of 97 out of 117 program recipients.Findings/Result: The findings show that the economic, social, and environmental performance of CSR programs in the agricultural sector positively and significantly influences corporate image and social welfare. Further analysis of the formulation of farming business analysis indicates that mining companies' CSR programs in agriculture can be assessed as sustainable.Conclusion: The three performance aspects of the agricultural CSR program affect the corporate image and social welfare of mining companies.Originality/value (State of Art): This research presents novelty in the management field with empirical research findings, especially related to the comprehensive influence on mining companies and surrounding communities by the three performances of the agricultural CSR programs implemented, which were not explored before.Keywords: agriculture program, corporate image, corporate social responsibility performance, mining company, social welfare